KEPEMIMPINAN SPIRITUAL KEPALA MADRASAH DALAM MENGEMBANGKAN NILAI HUMANISME - Rohim, Faidhur; Bagus Wijaya, Rahmadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to explore the application of spiritual leadership in the development of humanist values ​​at Madrasah Aliyah Miftahul Ulum Bengkak. This study uses a descriptive qualitative research design that aims to describe and analyze the implementation of spiritual leadership in the development of humanist values ​​at Madrasah Aliyah Miftahul Ulum Bengkak. The data for this study were obtained through interview, observation, and documentation methods. The results of this study indicate that the role of the madrasah principal as a role model for teachers and students, character development programs such as reading Istighosah and Asmaul Husna together, learning the Qur'an using the Ummi method, learning the book Al-Miftah Lil Ulum Sidogiri, congregational prayer activities, and religious activities involving all members of the madrasah that are in line with spiritual values ​​and humanist values.